Eco-Maqāṣid as an Integrative Islamic Response to Climate Change through a Conceptual Synthesis of Indonesian Ulama Council Fatwas - Fakhriy Ahmad; Ahmad Sudirman Abbas; Roma Wijaya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This article aims to analyze the Indonesian Ulema Council (MUI) Fatwa Number 86 of 2023 concerning the Law on Global Climate Change Control through the integration of two main conceptual frameworks: maqāṣid al-sharī‘ah as the normative framework of Islamic law and social-ecological systems (SES) as a systemic framework that emphasizes adaptive interactions between humans and the environment. Using a qualitative or a normative-conceptual approach based on literature, this study examines how the values of maqāṣid are articulated in the fatwa text and how the fatwa functions as an instrument of adaptive governance in strengthening the socio-ecological resilience of Muslims. The results of the analysis show that the MUI fatwa reflects an eco-maqāṣid perspective, namely an ecological reinterpretation of maqāṣid al-sharī‘ah that positions environmental protection (ḥifẓ al-bī’ah) as a contemporary expression of the objectives of classical sharia. This perspective shows that the fatwa plays a role not only as a legal product, but also as a moral and social mechanism that strengthens collective ecological awareness. Unlike previous research that tends to position fatwas as mere normative texts, this article emphasizes the dynamic function of fatwas within social-ecological systems. Theoretically, this research contributes an integrative perspective that enriches the epistemology of maqāṣid al-sharī‘ah by incorporating an ecological dimension; practically, it offers conceptual guidance for religious-based environmental governance and adaptive responses to the global climate crisis.